Study on energy characteristics in the triple jump in athletics - Lenuta, D.; Larion, A.; Rata, B. C. (Science, Movement & Health, 2021)
The main reason for choosing this topic is that in the literature there are not many studies on optimizing trial training for triple jump, junior girls and in choosing the most effective means of giving maximum efficiency in preparation. This could deprive specialist practitioners, a system of references required in the selection process in general training and then specialized in the corresponding age groups this. In preparing this paper we were motivated by the desire to express ourexperience in the 17 years of performancewith juniors and develop a methodical approach exactly in terms of efficiency the most commonly used means jumping event, namely triple jump and long jump at the highest level: -junior World Championships in Athletics.